Good data relations key to Indigenous research sovereignty: A case study from Nunatsiavut - Ortenzi, Kate; Flowers, Veronica; Pamak, Carla; Saunders, Michelle; Schmidt, Jörn; Bailey, Megan (Springer, 2025)
Although researchers are committed to Indigenous data sovereignty in principle, they fall short in returning data and results to communities in which or with whom they conduct their research. This results in a misalignment in benefits of research toward researchers and settler institutions and away from Indigenous communities. To explore this, we conducted a case study analyzing the rate researchers returned data to Nunatsiavut, an autonomous area claimed by Inuit of Labrador, Canada. We assessed the data return rate for all research approved by the Nunatsiavut Government Research Advisory Committee between 2011 and 2021. In two-thirds of projects, researchers did not return the data they had collected. Based on our results and their contextualization with researchers and Nunatsiavut Research Centre staff members, we compiled recommendations for researchers, academia, government bodies, funding bodies, and Indigenous research governance boards. These recommendations aim to facilitate data return, thus putting data sovereignty into practice.